2006
DOI: 10.1017/s1092852900014905
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Survey of Inmate Preferences for On-Site, Visiting Consultant, and Telemedicine Psychiatric Services

Abstract: Although inmates prefer the use of on-site mental health professionals for many mental health services, some inmates prefer visiting or telemedicine consultants for the evaluation of safety and sexual issues. Because telemedicine is efficient and readily available, its role in these areas requires further evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…42,43 As evidence suggests, video consultations can be successfully used for screening, diagnosis, disease management and counselling and, importantly, prisoners may prefer tele-psychiatry consultations (particularly in relation to childhood sexual abuse and other sexual concerns) compared with onsite consultations. 44 In addition, telemedicine seems to be useful for surgery, cardiology and emergency care and chronic disease management needs.…”
Section: Discussionmentioning
confidence: 99%
“…42,43 As evidence suggests, video consultations can be successfully used for screening, diagnosis, disease management and counselling and, importantly, prisoners may prefer tele-psychiatry consultations (particularly in relation to childhood sexual abuse and other sexual concerns) compared with onsite consultations. 44 In addition, telemedicine seems to be useful for surgery, cardiology and emergency care and chronic disease management needs.…”
Section: Discussionmentioning
confidence: 99%
“…All included studies examined video conferencing technology, which is a two-way interactive video and audio communication system. However, despite using the same technology, these studies did differ in the goal and target group: their focus ranged from, for example, video conferencing in forensic mental health in general ( 54 , 57 , 63 , 64 , 67 ) to specific target groups, for example, substance abusing patients ( 58 ), inmates with psychiatric problems ( 56 , 59 , 62 , 68 ), or both schizophrenic patient and family ( 52 , 53 ).…”
Section: Resultsmentioning
confidence: 99%
“…Many areas that have achieved success with prison telemedicine implemented models based on an initial decision made at a senior political level, with the source of this support varying, from Countrywide Acts and Laws, 46,125 to Ministry of Justice (or equivalent) 38,112,115,126 through to state level support. 65,69,95 This offer may be in the form of provision of funding, 70,7274,84,111,112 or use of a visionary or coalition-building approach to change. 95 Studies also reported that within the prison community itself, the governor or prison warden (the most senior member of the facility) also needs to be fully supportive of the proposed change within their domain.…”
Section: Resultsmentioning
confidence: 99%